Determining resuscitation outcomes in combat casualties: Design of the Deployed Hemostatic Emergency Resuscitation of Traumatic Exsanguinating Shock (Deployed HEROES) study. (12th August 2022) - Gurney, Jennifer M.; Staudt, Amanda M.; del Junco, Deborah J.; Holcomb, John; Martin, Matthew; Spinella, Phil; Trevino, Jennifer D.; Corley, Jason B.; Taylor, Audra L.; Rohrer, Andrew; Schreiber, Martin; Cap, Andrew
Abstract : Development and study design of the Deployed Hemostatic Emergency Resuscitation Of Traumatic Exsanguinating Shock (Deployed HEROES) Study- the first comprehensive analysis of military resuscitation practices in the deployed environment from 2001-2019 Abstract : BACKGROUND: During the course of the recent conflicts, the recommendations for resuscitation practices have evolved, but there has been no comprehensive comparative effectiveness study of these resuscitation strategies. The objective of this study was to describe the development and study design of the Deployed Hemostatic Emergency Resuscitation of Traumatic Exsanguinating Shock (Deployed HEROES) study—the first comprehensive analysis of military resuscitation practices in the deployed environment from October 2001 to October 2019. METHODS: This retrospective cohort study uses the Department of Defense Trauma Registry, Armed Services Blood Program database, and Military Trauma Mortality Review, while abstractors will use Theater Medical Data Store and Web Interface Patient Records to collect transfusion timing data. This study includes patients, who received blood products or died before receiving blood, treated at US military medical treatment facilities. The primary endpoints are survival at 6 hours, 24 hours, and 30 days postinjury. Secondary outcomes include infection, renal dysfunction, pulmonary dysfunction, and thromboembolic event. Exposure will be defined by blood product transfusion. Study groups will be frequency matched. Cox proportional hazards will compare patients who received warm fresh whole blood, low titer type-O whole blood, or only component therapy, while using adjustment for type of blood product transfused as a time-dependent covariate. Multilevel mixed-effects logistic regression will determine the effect of incompatible plasma in low titer type-O whole blood. RESULTS: An analysis plan for the Deployed HEROES study was developed with the aim of minimizing bias. CONCLUSION: This study will inform the optimal resuscitation strategies, which will potentially have a substantial impact on combat mortality. If whole blood is found to be the optimal transfusion strategy, this finding will be crucial in future operating environments involving dispersed medical assets. These results will provide critical information necessary for combat casualty care guidelines. LEVEL OF EVIDENCE: Prognostic and epidemiological; Level III. Abstract :